2020
DOI: 10.1038/s41598-019-56949-z
|View full text |Cite
|
Sign up to set email alerts
|

MIF gene rs755622 polymorphism positively associated with acute coronary syndrome in Chinese Han population: case–control study

Abstract: Macrophage migration inhibitory factor (MIF) has been recognized as a major player in the pathogenesis of atherosclerosis. This study determined the association between polymorphisms of MIF gene and acute coronary syndrome (ACS). The polymorphism of MIF gene (rs755622, rs1007888 and rs2096525) was analyzed in 1153 healthy controls and 699 ACS cases in Chinese Han population. Plasma MIF level was also measured in part of ACS patients (139/19.9%) and healthy controls (129/11.2%) randomly. Most participants inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…Our results are in good agreement with data of other groups indicating that high production of MIF is correlated with an increased susceptibility for a large number of inflammatory and metabolic diseases including chronic kidney failure [75][76][77][78][79]. However, in renal pathologies, MIF seems to act according to a model of antagonistic pleiotropism, in fact, in different clinical situations and in different stages of renal pathology it can exert both harmful and protective effects [47] which can be likened to the story of Dr. Jekyll and Mr. Hyde.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in good agreement with data of other groups indicating that high production of MIF is correlated with an increased susceptibility for a large number of inflammatory and metabolic diseases including chronic kidney failure [75][76][77][78][79]. However, in renal pathologies, MIF seems to act according to a model of antagonistic pleiotropism, in fact, in different clinical situations and in different stages of renal pathology it can exert both harmful and protective effects [47] which can be likened to the story of Dr. Jekyll and Mr. Hyde.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we observed that plasma MIF level was significantly elevated in CAD patients carrying of MIF gene rs755622 CC genotype. This finding was similar to our previous study, which showed MIF levels in ACS patients with CC genotype was significantly higher than ACS patients carrying GG genotype of MIF gene rs755622 41 . Ji et al 40 also reported that the plasma MIF level was higher in MIF rs755622 C allele carriers than in G allele carriers.…”
Section: Discussionsupporting
confidence: 92%
“…The MONICA/KORA Augsburg study suggested that rs755622 C allele and rs2070766 G allele were related to the higher risk for CAD in German females after 10 years follow-up 10 . Another case–control study showed that MIF gene rs755622 C allele was also associated with increased risk of ACS in a Chinese Han population 41 . Our previous study which conducted in a Kazakh population, a Chinese minority ethnic, found that the frequencies of MIF rs755622 CC genotype and C allele were significantly higher in CAD patients than that in control subjects 42 .…”
Section: Discussionmentioning
confidence: 99%
“…All the recruited participants were from Urumqi, excluding the surrounding and prefecture area. The design scheme of the study has been previously reported (24).…”
Section: Study Design and Populationmentioning
confidence: 99%